PLA2R1 Overexpression Causes Podocyte Injury by Inhibiting the Cell Cycle: A Clinical Cross-Sectional Investigation and Cellular Study - Liang W; Zhang H; Wu Y; Lai Z; Zhang W; Cao Y; Tan L; Xiong Z; Yang G; Xiong Z (International Journal of Nephrology and Renovascular Disease)
Wei Liang,1,2 Hua Zhang,2 Yi Wu,3 Zhiwei Lai,2 Weiqiang Zhang,3 Yuhao Cao,4 Lishan Tan,2 Zibo Xiong,2 Guang Yang,2 Zuying Xiong1,2 1Department of Nephrology, School of Clinical Medicine, Peking University Shenzhen Hospital, Anhui Medical University, Shenzhen, Guangdong, 518036, People’s Republic of China; 2Division of Renal Medicine, Peking University Shenzhen Hospital, Peking University, Shenzhen, 518036, People’s Republic of China; 3Institute of Nephrology, Shenzhen Peking University-The Hong Kong University of Science and Technology Medical Center, Shenzhen, 518036, People’s Republic of China; 4Department of Statistics and Data Science, Southern University of Science and Technology, Shenzhen, 518055, People’s Republic of ChinaCorrespondence: Zuying Xiong, Email xiongzy2005@163.comAim: Phospholipase A2 receptor 1 (PLA2R1) is often overexpressed in 70% of primary membranous nephropathy (PMN) patients, with serum PLA2R1 antibodies and podocyte PLA2R1 antigens serving as key diagnostic markers. However, a minority of patients test positive for only the PLA2R1 antigen and negative for PLA2R1 antibodies, presenting distinct characteristics. This study investigated the underlying features and mechanisms in PLA2R1 antigen-positive PMN patients.Methods: 26 patients’ information was screened for analysis. And the effects of PLA2R1 overexpression on human podocytes (HPCs) was studied through cell experiments.Results: Clinical observations revealed that the median age of the 26 patients was 48.5 years, and the median onset time was 135 days. There was a significant negative correlation between blood albumin and antigen intensity. Cell studies demonstrated that PLA2R1 overexpression inhibited the proliferation and viability of HPCs. RNA sequencing and FACS assays revealed that PLA2R1 overexpression arrests HPCs at the S and G2/M phases.Conclusion: PLA2R1 overexpression affects the course of the PMN by inhibiting the podocyte cycle. This study suggests that PLA2R1-related PMN pathogenesis could involve an additional immune response, offering insights into PMN treatment development.Keywords: PLA2R1, membranous nephropathy, nephrotic syndrome, podocyte